Do Environmental Performance and Corporate Social Responsibility Disclosure Affect Financial Performance? - Ningrum Pramudiati; Rahandhika Ivan Adyaksana; Afrinia Susilowati (UNIB Press, 2022)
The Ministry of Environment determines the company's environmental management performance evaluation plan or PROPER in controlling environmental effects to improve the company's role in environmental protection plans. However, many companies still get a red or black PROPER rating. Therefore, this study aimed to test the effect of environmental performance and corporate social responsibility disclosure on the company's financial performance. The sample used in the mining sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period, amounting to 49 companies. The sampling technique in this study used a purposive sampling technique. The purposive sampling technique is a sample selection technique using criteria. According to the sample's criteria, this research selected 55 financial statements from 11 companies. The data in this study were analyzed using multiple linear regression. The results of this study indicate that environmental performance and CSR disclosure have a positive effect on the company's financial performance. Then, financial performance and Corporate Social Responsibility Disclosure have a simultaneous and positive impact on the company's financial performance. Research can be considered for mining companies to always pay attention to environmental performance due to company activities. In addition, companies must consistently implement Corporate Social Responsibility in carrying out their business activities. The implementation of sound environmental performance must also be accompanied by the implementation of good corporate social responsibility. The company's financial performance is getting better because these two things can synergistically affect the company's economic performance.